Assessment of Transitional Orbits from a High Eccentricity LEO to a Circumlunar Orbit - ALnidawi, Marwah Issa Abood; Saleh, Abdul-Rahman H. (Iraqi Journal of Science, 2024)
This study presents an evaluation of the achievability and execution of transitional orbits for spacecraft transitioning from a high eccentricity Low Earth Orbit (LEO) to a circumlunar orbit, with the point of distinguishing the foremost proficient and ideal trajectory while considering variables such as velocity and required fuel. Transitional orbits have a role in space exploration, and optimizing their characteristics can enormously advantage mission planning and spacecraft design. A numerical simulation model was developed to attain this objective, A gravity perturbations effect is included in the calculation of the transition. The model utilized progressed numerical integration strategies for exact trajectory analysis. Three cases were examined to investigate the impacts of varying eccentricity and the argument of perigee on the ideal transition, In the first case, eccentricity values of [0.001, 0.01, 0.1] were inspected, whereas the argument of perigee was fixed at 80 degrees. Within the second case, the argument of perigee values of [80, 170, 260] was considered, with the eccentricity fixed at 0.1. The third case included at the same time varying the eccentricity and argument of perigee values. The results showed that the three cases agreed the most favorable transition occurred when eccentricity was set to 0.001 and the argument of perigee was set to 260 degrees. This produced a velocity increase of 2.195694 km/s, which is the lowest increase in ΔV, a metric used to measure fuel efficiency and power required. This finding also demonstrated the lowest change in eccentricity, the lowest change in inclination, and the lowest change in the ascending node, all of which are indicative of increased orbit stability.